2005
DOI: 10.18553/jmcp.2005.11.9.746
|View full text |Cite
|
Sign up to set email alerts
|

Product-Line Extensions and Pricing Strategies of Brand-Name Drugs Facing Patent Expiration

Abstract: This study provided some support for the alternative explanation to brand loyalty that a new product-line extension introduced for an original brand helps the original price be rigid despite the entry of generic drugs facilitated by the 1984 Drug Price Competition and Patent Term Restoration Act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…The problem of LASA medication packaging and labelling has grown and requires a policy response Design: survey study Phillips and Williams (2006) [21] Type: journal article Medical errors involving LASA neuromuscular blocking medications continue to result in patient morbidity and mortality Design: professional organisation statement James et al (2009) [8] Type: journal article Development of medication error reduction strategies is hampered by differences in definitions for dispensing errors, error rate and classification of error types Design: review Ashcroft et al (2005) [22] Type: journal article A wide range of medication errors occur in community pharmacies Design: prospective study Peterson et al (1999) [23] Type: journal article Dispensing errors occur in greater numbers than those reported to regulatory authorities and appear to be caused by high prescription volumes, fatigue and overwork Design: survey study Hong et al (2005) [24] Type: journal article Product line extensions help price rigidity in original brands Design: retrospective follow-up study AHA (2005) [25] Type: grey literature Provides case studies and an action agenda for reducing errors from LASA drugs Design: medication safety brief Aronson (2004) [26] Type: journal article Regulatory authorities and manufacturers should be vigilant when naming new drugs and formulations, in order to avoid drug name confusion Design: editorial Lambert et al (2010) [27] Type: journal article Clinician and lay person ability to identify spoken drug names is affected by signal-to-noise ratio, subjective familiarity, prescribing frequency and the similarity of drug names Design: laboratory experiment Kenagy and Stein (2001) [28] Type: journal article Drug names, labels and packaging are not chosen and designed in accordance with human factors principles and this contributes to medication errors that cause patient injuries and deaths Design: overview Santell and Cousins (2005) [29] Type: journal article Efforts by regulatory authorities, drug manufacturers, pharmacists, other health care professionals and patients can reduce medication errors Design: overview Schwab et al (2002) [30] Type: journal article Using trade names and omitting INNs can result in serious adverse drug events by overdose Design: clinical observation McCoy (2005) [31] Type: journal article Evaluation of potential LASA medication errors should occur proactively Design: case study ACSQHC (2002) [32] Type: grey literature Report seeks to increase general understanding of things that can go wrong with medicines, the size and nature of the problem in Australia, strategies that can make a difference and national directions being taken to improve medication safety Des...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of LASA medication packaging and labelling has grown and requires a policy response Design: survey study Phillips and Williams (2006) [21] Type: journal article Medical errors involving LASA neuromuscular blocking medications continue to result in patient morbidity and mortality Design: professional organisation statement James et al (2009) [8] Type: journal article Development of medication error reduction strategies is hampered by differences in definitions for dispensing errors, error rate and classification of error types Design: review Ashcroft et al (2005) [22] Type: journal article A wide range of medication errors occur in community pharmacies Design: prospective study Peterson et al (1999) [23] Type: journal article Dispensing errors occur in greater numbers than those reported to regulatory authorities and appear to be caused by high prescription volumes, fatigue and overwork Design: survey study Hong et al (2005) [24] Type: journal article Product line extensions help price rigidity in original brands Design: retrospective follow-up study AHA (2005) [25] Type: grey literature Provides case studies and an action agenda for reducing errors from LASA drugs Design: medication safety brief Aronson (2004) [26] Type: journal article Regulatory authorities and manufacturers should be vigilant when naming new drugs and formulations, in order to avoid drug name confusion Design: editorial Lambert et al (2010) [27] Type: journal article Clinician and lay person ability to identify spoken drug names is affected by signal-to-noise ratio, subjective familiarity, prescribing frequency and the similarity of drug names Design: laboratory experiment Kenagy and Stein (2001) [28] Type: journal article Drug names, labels and packaging are not chosen and designed in accordance with human factors principles and this contributes to medication errors that cause patient injuries and deaths Design: overview Santell and Cousins (2005) [29] Type: journal article Efforts by regulatory authorities, drug manufacturers, pharmacists, other health care professionals and patients can reduce medication errors Design: overview Schwab et al (2002) [30] Type: journal article Using trade names and omitting INNs can result in serious adverse drug events by overdose Design: clinical observation McCoy (2005) [31] Type: journal article Evaluation of potential LASA medication errors should occur proactively Design: case study ACSQHC (2002) [32] Type: grey literature Report seeks to increase general understanding of things that can go wrong with medicines, the size and nature of the problem in Australia, strategies that can make a difference and national directions being taken to improve medication safety Des...…”
Section: Resultsmentioning
confidence: 99%
“…new formulation or modified molecule) of an existing product. [24] Brand extensions are an effective way to support price rigidity in products that are going off-patent and can result in products with names similar to existing products. Brand extension leads to problems arising with drug names, particularly where products with different dosage forms are only indicated by the use of suffixes (e.g.…”
Section: Types Of Problemsmentioning
confidence: 99%
“…Hong et al [8] In order to guarantee the flow of high benefits, pharmaceutical firms reinforce their competitive position by spending enormous amount of resources in marketing activities. In this sense, Gagnon and Lexchin [6] showed that pharmaceutical companies spent in promotion and marketing activities twice as they did in R&D (57,500 million USD versus 29,500 million USD in the USA for the year 2004).…”
Section: Some Side Effects Of Patentsmentioning
confidence: 99%
“…In particular, brand-name drug firms can limit generic entry by launching the so called 'pseudogenerics' (Kong 2009) or even by taking over generic firms (European Commision 2009). Alternatively, pharmaceutical firms can launch product-line extensions (Hong et al 2005). A line extension is a variation of an existing product or a modification of an existing molecular entity.…”
Section: Introductionmentioning
confidence: 99%
“…strictly new. 3 Hong et al (2005) report that only 15% of the 1,035 new drugs approved by the US Food and Drug Administration from 1989 through 2000 were innovative drugs. In Spain, according to the Ministry of Health and Consumption (2005), 782 new specialities were registered in 2004, from which 747 were based in already known chemical ingredients (about 300 were generic drugs) and 35 in new ones.…”
Section: Introductionmentioning
confidence: 99%